The General Yard Allocation Problem - CHEN, Ping (Institutional Knowledge at Singapore Management University, 2003)
The General Yard Allocation Problem (GYAP) is a resource allocation problem faced by the Port of Singapore Authority. Here, space allocation for cargo is minimized for all incoming requests for space required in the yard within time intervals. The GYAP is NP-hard for which we propose several heuristic algorithms, including Tabu Search, Simulated Annealing, Genetic Algorithms and the recently emerged “Squeaky Wheel” Optimization (SWO). Extensive experiments give solutions to the problem while comparisons among approaches developed show that the Genetic Algorithm method gives best results.